Profile of Preschool Diarrhoea in a Rural Community - Mishra, V N; Garg, S K; Bhatnagar, M; Singh, J V; Chopra, H; Singh, R B (Indian Journal of Community Health, 1990)
A significant new knowledge acquired in the last decade on the aetiology, epidemiology, pathogenesis, immunology and treatment of acute diarrhoea provided a solid basis for the immediate attack on the problem. Although acute diarrlioeal disease is one of the major causes of morbidity and mortality among children yet only few studies on diarrhoea related morbidity and mortality are available. An attempt was Made in the present study to determine the magnitude of the problem of diarrhoea among preschool children and prevailing health practices so as to plan the action for the control of diarrhoeal diseases among preschool children in rural community.